AIR POWER AND REGIONAL SECURITY: ASSESSING INDONESIA’S AIR DEFENSE STRATEGY IN THE CONTEXT OF ASEAN REGIONAL - Refa Defanda; Aswin Ariyanto Azis (Indonesian Association for International Relations, 2026)
This study examines Indonesia's air defense policy within the context of ASEAN regional security. It employs the concept of Air Superiority alongside the Regional Security Complex Theory (RSCT) to analyze significant acquisitions such as the Rafale fighter jet, the F-15EX, participation in the KF-21 Boramae program, the deployment of the NASAMS system, and multilateral exercises like Garuda Shield. The findings indicate that Indonesia's modernization efforts are a response to challenges to its sovereignty, frequent violations of its airspace, and emerging threats including drone and missile proliferation. Regionally, these enhancements to Indonesia's air power are altering the security balance in relation to well-equipped ASEAN neighbors such as Singapore and Malaysia, while also reinforcing ASEAN's cooperative but non-binding security mechanisms. The primary contribution of this study is its demonstration that Indonesia's modernization efforts strengthen national deterrence and promote regional stability, while also highlighting the limitations of ASEAN's institutional framework. Future research should include operational assessments and scenario-based exercises to better anticipate Indonesia's evolving role in ASEAN security